Wind energy conversion systems analysis of PMSG on offshore wind turbine using improved SMC and Extended State Observer. (December 2020) - Pan, Lin; Shao, Chengpeng
Abstract: In this paper, an improved Sliding Mode Control(SMC) is proposed based on the Wind Energy Conversion System(WECS), which is with offshore wind turbine Permanent Magnet Synchronous Generator(PMSG) connected to the grid. Moreover, an aerodynamic torque observer is presented to improve the performance of Maximum Power Point Tracking(MPPT). Since the wind energy conversion system is a complicated nonlinear system, an enhanced reach law of sliding mode controller is designed to reduce the chattering issue. Compared to traditional control methods, the simulation results show that the control method proposed in this paper significantly improves the stability and robustness of PMSG-Based WECS in the area of MPPT. Highlights: A sliding mode control method with extant state observer is proposed for MPPT. A sliding mode control method based on a new approach rate is designed. The anti-interference ability is signi_cantly improved by the proposed method. The feed-forward compensation is added on grid voltage orientation.